Expressive Arts Activities as Tools to Enhance the Education of Clinical Psychologists: A Qualitative Study - Bertelli, Rosangela (Advances in Social Sciences Research Journal, 2019)
Educating clinical psychologists through the use of expressive arts activities allows the novices to become aware of those cognitions that flow without their conscious control, and educating cognitive-behavioural clinical psychologists through the use of expressive arts activities allows the novices to grasp how the four elements (circumstances, cognitions, emotions, and behaviours) of the cognitive-behavioural model of learning are all entwined. Such understanding is central to the ability to recognise maladaptive or dysfunctional symptoms. The research problem here was: Would the novices remain on the expressive art activity just observing their own flow of automatic cognitions, without complying with those thoughts and associated emotional reactions? Eighteen female graduate students were being educated through the use of expressive arts activities in order to comprehend the cognitive-behavioural psychotherapies. Qualitative data obtained through descriptive written reports made by the students themselves were triangulated and data analysis shaped the scenario that the expressive arts activities facilitate the development of an attentive awareness that allows for the witnessing of one’s streams of thoughts and associated emotions. Expressive arts activities do add something extra that make the learning process more intense, better, more captivating, and tangible to the novices.